Implementasi Algoritma A* (A-Star) untuk mencari Rute Tercepat dari Bandara Soekarno Hatta ke Destinasi Kota Tua Jakarta - Arfadhillah, Zahra; Akbar, Yuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The tourism sector is an economic sector that is growing rapidly. One of the best destinations that can be used as a tourist destination in DKI Jakarta is the Old City of Jakarta. The Old City of Jakarta has easy access and very affordable costs. There are many roads to the Old City of Jakarta, but the road to the Old City of Jakarta is very far away and has traffic congestion, especially towards the weekend, which could potentially make it difficult for tourists who want to visit. Therefore, we need an effective method that can help find the route with the shortest distance and fastest travel time. In this research, the method that can be used to find the fastest path or route is the A*Star algorithm. The results obtained after examining three routes (Jalan Kapuk Kamal Raya, Jalan Peta Barat and Jalan Raya Daan Mogot), obtained the fastest route with a distance of 5,881.5 KM, namely the Jalan Kapuk Kamal Raya route. By applying this method, it is hoped that it can solve the problem of determining the fastest route to the tourist location of the Old City of Jakarta.